Impact of spike anneal on ultra shallow junction formation - Lai, Chung Woh (2008)
This report explains the need for ultra shallow junctions for modern day CMOS devices, how spike anneal can help achieve this, reviews the important parameters if this process and how these parameters affect the performances of the CMOS transistors.